1988
DOI: 10.1111/j.1600-0714.1988.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretor status, candidal carriage and candidal infection in patients with diabetes mellitus

Abstract: One hundred and nine patients with diabetes mellitus and 100 age‐, sex‐ and denture‐status‐matched, non‐diabetic individuals were investigated prospectively. Comparison was made of oral candidal carriage, clinical infection and inherited ability to secrete blood group antigens in saliva. Diabetic patients had a significantly higher prevalence of oral candidal carriage and infection (P < 0.001) than non‐diabetic individuals, but the candidal load between the 2 groups, was not significant. A comparable proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
52
6
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 24 publications
12
52
6
2
Order By: Relevance
“…Gray et al proposed that there is no correlation between glycemic level and the Candida carriage rate [14]. Yet another study by Lamey et al showed the lack of association between HbA1c or blood glucose level and the Candida carriage rate [15]. Similar reports were also given by Kumar et al who stated that glycemic control and antidiabetic drugs have no correlation with the Candida carriage [16].…”
Section: Discussionsupporting
confidence: 60%
“…Gray et al proposed that there is no correlation between glycemic level and the Candida carriage rate [14]. Yet another study by Lamey et al showed the lack of association between HbA1c or blood glucose level and the Candida carriage rate [15]. Similar reports were also given by Kumar et al who stated that glycemic control and antidiabetic drugs have no correlation with the Candida carriage [16].…”
Section: Discussionsupporting
confidence: 60%
“…It was recently noted that epithelial cells from diabetic patients had a higher level of yeast adhesion than cells from nondiabetic controls (Darwazeh e t al., 1990 ; Segal e t al. , 1984), suggesting a correlation between I. POLACHECK a n d O T H E R S the in vitro adhesion ability of the former cells and the known increased susceptibility of these patients to oral, vaginal and cutaneous candidiasis (Lamey et al, 1988;Segal et al, 1984;Segal, 1994;Srebrnik & Segal, 1990). Contrary to this, our study showed no difference in adherence to BECs from diabetics and healthy subjects, questioning the existence of such a correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are more clinical Candida infections in diabetic patients than non-diabetic individuals (Lamey et al 1988, Darwazeh et al 1990). A high blood glucose level has been shown to associate with candidiasis (Hill et al 1989) and a high salivary glucose level with high salivary yeast counts .…”
Section: Candida Infectionsmentioning
confidence: 99%